2023
DOI: 10.1186/s13046-022-02568-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of toxicity burden for FDA-approved immune checkpoint inhibitors in the United States

Abstract: Background Immune-related adverse events (irAEs) are a common phenomenon in cancer patients treated with immune checkpoint inhibitors (ICIs). Surprisingly, the toxicity burdens of these irAEs have not been illustrated clearly. In this study, we analyzed irAEs for seven FDA-approved ICIs in cancer treatment to show the pattern of toxicity burden among cancer patients. Methods irAEs associated with seven FDA-approved ICIs, including three PD-1 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Only 2 peer-reviewed publications were included, and most studies were available only as abstracts, making it difficult to assess the risk of bias. Additionally, our study assumed that the type of cancer does not impact immunotherapy toxicity, while some studies have suggested that the risk of immunotherapy toxicity may be higher in certain types of cancer, such as lung cancer ( 28 , 29 ). Our analysis only included one RCT that evaluated the safety profile of ICT versus ICT with VEGFi combination therapy in non-small cell lung cancer ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 peer-reviewed publications were included, and most studies were available only as abstracts, making it difficult to assess the risk of bias. Additionally, our study assumed that the type of cancer does not impact immunotherapy toxicity, while some studies have suggested that the risk of immunotherapy toxicity may be higher in certain types of cancer, such as lung cancer ( 28 , 29 ). Our analysis only included one RCT that evaluated the safety profile of ICT versus ICT with VEGFi combination therapy in non-small cell lung cancer ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…During ICIs treatment, irAEs occur unpredictably and can be life-threatening. 5,23 It is essential to have a deeper understanding of irAEs in order to effectively manage the benefit-to-risk ratio of ICIs. In this observational study, we evaluated the association between irAEs and response rate and survival in NSCLC patients treated with PD-1 inhibitors-based combination therapy, especially in combination with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Male patients are more prone to respiratory and thoracic disorders, whereas reproductive system and breast diseases prevail among female patients. The results indicate that sex or age contributes to the occurrence of different irAEs, requiring a heightened awareness of respiratory and genitourinary toxicities for male patients, while female patients need increased prevention of reproductive system toxicities ( 92 ). Additionally, multiple studies have demonstrated that ICIs can induce various dermatological adverse events (DAEs), such as autoimmune bullous dermatosis, acute generalized exanthematous pustulosis, and psoriasiform rash ( 93 ).…”
Section: Adverse Eventsmentioning
confidence: 99%